‘The Great Heroes’ day is much holier for us than religion’: The commemoration of martyrs in post-war Tamil communities - Mantovan, G. (Religion)
After the defeat of the Liberation Tigers of Tamil Eelam (LTTE) in 2009, all the martyrs’ cemeteries were destroyed by the Sri Lankan army. Yet Tamil activists have continued to commemorate the fallen fighters each year during Maaveerar Naal (‘Great Heroes’ Day’). This ceremony both sustains Tamil activism and contributes to the transmission of a national memory of a people oppressed yet still resisting Sinhala nationalism – a commemorative practice first instituted by the LTTE. This article examines how the LTTE, and later Tamil activists and diaspora associations that have continued its legacy, mobilised religious and cultural symbols to produce a form of civil religion in which the martyrs are venerated as deities and the cemeteries function as sacred sites. Drawing on participant observation in Jaffna, London, and Paris, it analyses the relationship between religion and heritage as manifested through this commemoration. By reworking elements of Tamil heritage, the LTTE presented itself as the defender of Tamil culture while rendering the veneration of the martyrs both legitimate and intelligible within that cultural framework.